La revitalisation des centres-bourgs en Livradois Forez, des projets d’urbanisme singularisés par le contexte d’intervention rural ? - Yoan Miot; Sarah Dubeaux (Territoire en Mouvement)
Local authorities’ actions in rural municipalities have particular characteristics considering land-use and planning: lack of finances and engineering, social and spatial proximity between local authorities and inhabitants. Our research focus on characteristics of urban projects with the case of Livradois Forez: a French rural and mountain area localized in center of France where the Regional Natural Park developed a process of revitalizing small centers. In this article, we show that particularities in rural context led to new and shared methodology and to innovative system of actors contrasted with urban realities. This network becomes local development authority who manage the development and realization of revitalizing projects. Furthermore, we show that these innovations are the result of ten years with local experimentations without State’s support but are fragilized by nowadays austerity strategies and new national (top down) programs with rural considerations.